Examining the benefits of renewable energy: wind power - Reker, Benjamin A. (Kansas State University, 2014)
This report provides a summary of the state of wind energy in the United States, the policy instruments used to encourage renewable energy and the research finding on the benefits of wind energy. It provides insight from a Texas case study, as well as international perspectives. Renewable and non-renewable energy sources are defined and compared. The report discusses the negative environmental impacts of conventional power generation, in contrast to lack of emissions from renewable power. Background information on U.S. energy consumption and climate change are provided. The primary policies used to promote renewable energy, which apply to wind power, are explained. The economic theory behind the relationship of subsidies and externalities is explained, as well as the implications that firm profit-maximization has on market outcomes. This report finds that the benefits derived from wind energy production and the promoting policies outweigh the costs associated with them.
Keywords: Economics; Renewable; Wind power; United States Policy; Sustainability; Wind energy; Alternative Energy (0363); Economics (0501); Environmental economics (0438)